What Drives Quality Physical Education? A Systematic Review and Meta-Analysis of Learning and Development Effects From Physical Education-Based Interventions - Dudley, Dean; Mackenzie, Erin; Van Bergen, Penny; Cairney, John; Barnett, Lisa (Frontiers in Psychology, 2022)
Abstract Objective: To determine the effects of learning interventions aimed at optimising the quality of physical education (PE) on psychomotor, cognitive, affective and social learning outcomes in children and adolescents. Design: A systematic review and meta-analysis. Data sources: After searching PsycInfo, ERIC, and SportDiscus electronic databases, we identified 135 eligible studies published between January 1, 1995 to May 1, 2021. Eligibility criteria for selecting studies: We included randomised controlled trials, quasi-experimental studies, and controlled trials that assessed the effect of a PE-based intervention against one of the four identified learning domains in youth at school (aged 5–18 years). Results: One hundred and thirty five (135) studies with over 42,500 participants and 193 calculated effect sizes were included in the study. The mean effect across all the learning and development outcomes was small to medium (Cohen’s d=0.32, 95% confidence interval [CI] (0.27 to 0.37). When adjusted for publication bias using the Duval and Tweedie (2000) Trim and Fill Method, this mean effect size increased to d=0.40 (CI=0.34-0.46). Effect sizes varied significantly based on learning and development outcomes. Interventions that consistently report above or below the mean d=0.40 effect are identified based on learning outcome. The greatest effects across interventions were witnessed in psychomotor learning outcomes (d=0.52) followed by affective (d=0.47), social (d=0.32), and cognitive (d=0.17) learning outcomes. A minority (less than 10%) of PE interventions captured by this systematic review and meta-analysis reported having a negative effect on student learning and development. Conclusion: The interventions with the greatest effects on student learning and development were dependant on the learning domains. Some PE interventions with a pedagogical focus such as games-based approaches, TARGET/Mastery Teaching, and Sport Education were found to be strong investments across multiple domains. The evidence is limited however by consistency in intervention dosage, study design, and data collection instruments. The study received no internal or external funding and was not prospectively registered.